KEBIJAKAN PENGEMBANGAN KAWASAN WISATA BAHARI BERBASIS KEARIFAN LOKAL DAN PENGUATAN KELEMBAGAAN DESA DALAM RANGKA MENINGKATKAN KESEJAHTERAAN MASYARAKAT - Yuni Ratna Sari; Dian Kagungan (Jurnal Ilmiah Econosains, 2016)
Abstract The long term goal of this research resulted in Coastal Rural Poverty Alleviation Model Optimization Through Marine Tourism Area Development Policy Based Local Wisdom and Institutional Strengthening of the village in order to improve the welfare of society. The conclusion from this study are: (1) Region Ecotourism Kiluan Bay manifested in the form of training, turtle conservation, as well as provide strategies for promotion or marketing. The output of these training activities is to build awareness together in building businesses and collective marketing and environmental protection Kiluan Bay. (2) The strategy for improving institutional capacity at the village level: encourage institutions pekon / villages to understand their duties and functions, institutional strengthening village / pekon open in the sense of community participation in development activities undertaken. (3) The strategy of empowerment of coastal communities through the management of the Gulf tourist area Kiluan among others through trainings, planting mangroves, coral reefs. (4) Strategic management of coastal areas through ecotourism development Kiluan Bay: trying to get support from local and central government, promotion in various social media conducted since 2005, involved in promosi- sale by local governments and the provincial government. Suggestions / recommendations from the results of our study are: (1) Improved coordination and policy coherence of the program between the relevant agencies in the in order to develop tourist areas Kiluan Bay, (2) Strengthen institutional level Village / Pekon, (3) improvements to the road infrastructure Kiluan Gulf region and complements other infrastructure in order to support the advancement of ecotourism Kiluan Bay, (4) development of community-based ecotourism, assisted by NGOs and local government and other stakeholders. (5) Improving the quality Source Human power through a system of formal and non-formal (6) Institutional strengthening of village-based local wisdom. Keywords: Model, poverty alleviation coastal villages, nautical tourism, strengthening village institutions, public welfare